EDUCATIONAL TECHNOLOGY PROCESS IN EARLY CHILDHOOD EDUCATION INSTITUTIONS - Khambali, Khambali; Priatna, Tedi; Zakiah, Qiqi Yuliati (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2022)
The purpose of this study is to describe a number of media in the form of websites, applications and information systems that are used as the use of technology in learning in early childhood education institutions. Descriptive-analytical literature becomes the method in this research. The results of the study show that technology is an integral part of education. All activities use technology even in a simple way. In accordance with its essence is to facilitate the activities of educational actors. Educational technology can be defined as theory and practice in designing, developing, utilizing, managing, and assessing processes and resources for learning. The internet is one of the relevant media if it is used to support the quality of early childhood education. Because it can provide convenience and speed in conveying information so that the learning process can run effectively and efficiently. The internet can provide several facilities and services/applications such as: e-learning, LMS, Internet Applications, Youtube and others to be used in the learning process at early childhood education institutions.